Design of ionic liquid-based polyelectrolytes by combining 'nanostructurisation' and 'zwitterionisation'. Issue 6 (11th January 2016) - Matsumoto, Takuro; Ichikawa, Takahiro; Ohno, Hiroyuki
Abstract : We have designed nanostructured polyelectrolytes through the co-aggregation of micelles bearing polyzwitterion and lithium salts. Abstract : We have prepared poly(ammonium-based zwitterion) block copolymers forming nanosegregated assemblies. The incorporation of lithium bis(trifluoromethanesulfonyl)imide (LiTf2 N) into the assemblies, setting up ionic liquid-like ion pairs of the ammonium cations and Tf2 N anions, endowed the polyzwitterion domains with ion transporting abilities.